2003
DOI: 10.1590/s0100-41582003000300004
|View full text |Cite
|
Sign up to set email alerts
|

Chemigation with benomyl and fluazinam and their fungicidal effects in soil for white mold control on dry beans

Abstract: The effectiveness of fungicides in controlling white mold (Sclerotinia sclerotiorum) of dry beans (Phaseolus vulgaris) was evaluated when they were applied through irrigation water directly onto the plants or only to the soil. Two field trials were installed in April 1998 and April 1999 in Viçosa, MG. Trials were conducted as a (2 x 3) + 1 factorial: two fungicides x three application modes + one untreated control. The fungicides were benomyl (1.0 kg a.i. ha-1) and fluazinam (0.5 l a.i. ha-1). The three applic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
8
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 12 publications
2
8
0
Order By: Relevance
“…Moreover, greater sclerotial weight reduction was observed for fluazinam ground application. This is consistent with a previous study in which fluazinam application by backpack ground application (667 L ha -1 ) was compared to chemigation (3.5 mm) and showed that ground application reduced the weight and number of S. sclerotiorum sclerotia collected after dry bean harvest (Vieira et al, 2003). The same authors also reported that fluazinam can control white mold when applied directly to the soil surface and is superior to benomyl (systemic) in reducing incidence and severity.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Moreover, greater sclerotial weight reduction was observed for fluazinam ground application. This is consistent with a previous study in which fluazinam application by backpack ground application (667 L ha -1 ) was compared to chemigation (3.5 mm) and showed that ground application reduced the weight and number of S. sclerotiorum sclerotia collected after dry bean harvest (Vieira et al, 2003). The same authors also reported that fluazinam can control white mold when applied directly to the soil surface and is superior to benomyl (systemic) in reducing incidence and severity.…”
Section: Discussionsupporting
confidence: 91%
“…Secondary infection of leaves, petioles and stems is by mycelium through direct contact with infected flowers (Abawi et al, 1975). An integrated disease management approach for S. sclerotiorum control is recommended, including use of certified seed, crop rotation with a non-host monocot crop, selection of upright cultivars, tilling soil, routine cleaning of agricultural implements, biological control, and fungicidal control (Harikrishnan and del Río, 2006;Lehner et al, 2015;McCreary et al, 2016;Miklas et al, 2013;Paula Júnior et al, 2009bVieira et al, 2003Vieira et al, , 2010Vieira et al, , 2012.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The form of fungicide application (conventional application) coud be another factor to be considered when analyzing this low level of pathogen control. Oliveira et al (1995) and Vieira et al (2003) stated the importance of application know-how in relation to fungicides used to control the white mold, reinforcing the evident efficiency of fumigation and chemigation in detriment of compared to conventional application methods. …”
Section: Comparison Of Chemical and Biological Control In Vivomentioning
confidence: 99%
“…However, in many cases, especially for high value crops or highly specialized farms these methods are insufficient. Fungicides play the most important role in successful and effective white mold management (Mueller et al 2002a;Vieira et al 2003;Paula Junior et al 2009;Derbyshire and Denton-Giles 2016). For instance, soil fumigation with metham-sodium decreased the amount of resting propagules (Ben-Yephet et al 1986).…”
Section: Introductionmentioning
confidence: 99%